A Longitudinal Hepatitis B Vaccine Cohort Demonstrates Long-lasting Hepatitis B Virus (HBV) Cellular Immunity Despite Loss of Antibody Against HBV Surface Antigen. (7th April 2016) - Simons, Brenna C.; Spradling, Philip R.; Bruden, Dana J. T.; Zanis, Carolyn; Case, Samantha; Choromanski, Tammy L.; Apodaca, Minjun; Brogdon, Hazel D.; Dwyer, Gaelen; Snowball, Mary; Negus, Susan; Bruce, Michael G.; et al.
Abstract: Background. Long-lasting protection resulting from hepatitis B vaccine, despite loss of antibody against hepatitis B virus (HBV) surface antigen (anti-HBs), is undetermined. Methods. We recruited persons from a cohort vaccinated with plasma-derived hepatitis B vaccine in 1981 who have been followed periodically since. We performed serological testing for anti-HBs and microRNA-155 and assessed HBV-specific T-cell responses by enzyme-linked immunospot and cytometric bead array. Study subgroups were defined 32 years after vaccination as having an anti-HBs level of either ≥10 mIU/mL (group 1; n = 13) or <10 mIU/mL (group 2; n = 31). Results. All 44 participants, regardless of anti-HBs level, tested positive for tumor necrosis factor α, interleukin 10, or interleukin 6 production by HBV surface antigen–specific T cells. The frequency of natural killer T cells correlated with the level of anti-HBs ( P = .008). The proportion of participants who demonstrated T-cell responses to HBV core antigen varied among the cytokines measured, suggesting some natural exposure to HBV in the study group. No participant had evidence of breakthrough HBV infection. Conclusions. Evidence of long-lasting cellular immunity, regardless of anti-HBs level, suggests that protection afforded by primary immunization with plasma-derived hepatitis B vaccine during childhood and adulthood lasts at least 32 years.